SIMULATION MODELLING METHODS FOR IDENTIFICATION AND FORECASTING OF KEFIR PRODUCTION - Nazoykin, Evgeny; Blagoveshchensky, Ivan (Revista Inclusiones, 2020)
This article is devoted to urgent issues of optimization of production processes as exemplified by kefir production. In order to solve the highlighted issues, it is proposed to develop control subsystem on the basis of multi-agent simulation modelling. Aiming at development and implementation of the model, this article thoroughly analyzes kefir production at dairy factories. On the basis of analyzed regularities, recommendations are given for implementation of multi-agent simulation model of kefir production used for analysis of optimization and detection of bottlenecks of the production process using simulation experiment. AnyLogic simulation modelling tool was used for the analysis and implementation of the model. On the basis of experiments with simulation model, the quantitative indicators of production output are estimated and recommendations are given to plan and to control kefir production at similar factories.